Are hypervelocity impacts able to produce chondrule-like ejecta?. (1st November 2019) - Ganino, Clément; Libourel, Guy; Nakamura, Akiko M.; Michel, Patrick
Abstract: Chondrules are one of the major components of primitive meteorites. Their sphericity indicates they formed as molten fragments or droplets but conditions and mechanisms of chondrule formation remain unknown. A possible scenario is their formation during hypervelocity impacts and ejections. To challenge this idea, we prepared an experiment that reproduces analogous of iron metal -rich chondrules by impact between a glassy silicate projectile and a metallic steel target. The hypervelocity experiment setting allowed an impact velocity of 5 km/s, and was also designed to collect the ejecta. A scanning electron microscopy survey shows that silicate ejecta share several similarities with chondrules. They formed from a population of small melt fragments whose size distribution has the same shape as the size distribution of chondrules, with a shift in size: ejecta are about one order of magnitude smaller than typical chondrules (log( d chondrules /d ejecta ) =  1 . 3 − 0.7 + 0.5 ). We attribute this difference in size to the large discrepancy in the size of the impactors (only small 3 mm particle in our experiment versus km-scale planetesimal expected in an impact forming scenario for chondrules). The silicate ejecta formed in the ejecta plume contains numerous small size spherical iron metal beads. Such beads are also observed in numerous chondrules of CO chondrites specifically presented here but also documented in L and LL ordinary chondrites. Size distributions of metal beads in ejecta and chondrules of a carbonaceous chondrite used as reference material (Yamato 81020 CO) display a same shape but with a size shift, quite similar to the one observed between the ejecta droplets and the chondrules: the diameter of metal beads in ejecta is about one order of magnitude smaller than the diameter of the ejecta themselves (log( d ejecta /d metal beads in ejecta ) =  1 . 2 − 0.8 + 0.9 ), and the diameter of metal beads in chondrules is about one order of magnitude smaller than the diameter of the chondrules themselves (log( d chondrules /d metal beads in chondrules ) =  1 . 4 − 1.0 + 0.6 ). We attribute this size differences to the blast dynamics: for a same velocity and surface tension, fragments of silicate liquid will be stable when iron liquid fragments of similar size will be separated into smaller droplets. In our experiment, the biggest iron metal beads (∼7 μm) are within the mean size range of silicate ejecta and can be considered as analogous of the rare large rounded metallic grains (nearly the same size as chondrules) documented in CB chondrites. The textural analogies exposed here provide support for a production of chondrules by impact. Highlights: Silicate ejecta formed in impact experiment have several similarities with chondrules. Ejecta formed in the impact blast contains small iron metal beads. Size distributions of ejecta and chondrules similar but with size shift. Size distributions of metal beads in ejecta and chondrules close but with size shift. Textural analogies provide support for a production of chondrules by impact.